Atmospheric pressure plasma etching of Ti-6Al-4V using SF₆ - Bishop, Alex (Cranfield University, 2023)
Atmospheric pressure plasma (APP) etching using SF₆ has been shown to etch Ti- 6Al-4V (Ti64). Operating parameters for input power, SF₆ concentration and standoff distance were determined through previous work as 1.2 kW, 0.8 L min⁻¹ and 6mm respectively as the optimum values for etching using the Helios 1200 machine. By using various surface characterisation techniques, information over a broad range of spatial frequencies was obtained. By conducting stationary, dynamic and areal etching, the process has been shown a high degree of precision and material removal rates varying from 0.5 mm3 min⁻¹ to 2 mm³ min⁻¹ . This process preferentially etches the BCC β phase of Ti64 over the HPC α phase by∼50 %. It is proposed that this preferential etching of the β phase is due to both the crystal structure strength being weaker than the α phase and the BCC crystal structure being less dense than HPC, making it easier to remove more volume of material. The etching process is highly temperature dependent and preheating of the samples is required to achieve a clean trench. Significant amounts of redeposition also remain on the surface <2 µm which comprise of mostly fluorine and oxygen, but this is easily removed. The surface remains optically opaque after etching due to significant roughening of the surface, however negligible contamination remains. The proposed material removal mechanism is through the formation of volatile VFₓ and TiF₄ compounds.
Keywords: surface characterisation; spatial frequencies; stationary; dynamic; areal etching; material removal